Neurosurgical nurses’ perspectives of patient-reported outcomes: a qualitative study - Yu Han; Yanmei Wang; Yan Liu; Zezhou Wang; Xue Dong; Kui Fang (BMC Nursing)
Abstract Background Patient-reported outcomes (PROs) are critical in neurosurgical care for addressing post-discharge unmet needs (e.g., pain, functional impairments), yet traditional assessment models often neglect subjective experiences. Although PROs integrate patient perspectives with clinical indicators, improving diagnosis and care, significant variations exist in nurses’ understanding of PROs, potentially hindering implementation. This study explores neurosurgical nurses’ perspectives and experiences to inform a Nurse-led PROs System. Method Using purposive sampling, 15 neurosurgical nurses from two institutions participated in offline semi-structured interviews between December 2024 and January 2025. Interviews (30–60 minutes) explored PROs awareness, barriers, and application in practice. Data were transcribed verbatim and analyzed via the Kawakita Jiro (KJ) method to identify thematic patterns. Ethical approval was obtained (Lun Audit [2024] 222). Results Thematic saturation was reached after 15 interviews.The study identified six themes: (1) Prevailing challenges; (2) Cognitive level; (3) Patients’ medical experience; (4) Impact factors; (5) System support; (6) The ‘Shared decision-making discharge’ Model. Conclusions To address PROs implementation gaps, senior management must prioritize nurse training, digital infrastructure, and multidisciplinary collaboration. A Nurse-led PROs System should standardize post-discharge assessments, while the proposed “Shared Decision-Making Discharge” model could bridge patient-provider communication gaps. Future studies should test this model’s impact on care quality. Clinical trail number Not applicable.